Macro federalism and local finance - Shan, Anwar (ed.) (Washington, 2008)
The design of a federal system to deal with growth, stabilization, and regional and local development issues is the primary concern of this volume, edited by Anwar Shah. The book provides analytical tools to address issues arising from globalization, localization, and regional integration. It discusses tax harmonization issues associated with subnational value added tax administration. It provides a framework for fiscal discipline in a federal system. Lessons from international experiences from policies to deal with lagging regions are drawn. The book empirically examines the effect of fiscal decentralization on the overall size of the public sector. Finally, it draws lessons from industrial countries experiences on local governance. This important new series represents a response to several independent evaluations in recent years that have argued that development practitioners and policy makers dealing with public sector reforms in developing countries and, indeed, anyone with a concern for effective public governance could benefit from a synthesis of newer perspectives on public sector reforms. This series distills current wisdom and presents tools of analysis for improving the efficiency, equity, and efficacy of the public sector. Leading public policy experts and practitioners have contributed to the series.
Keywords: Intergovernmental fiscal relations